Millenial Islamist in Contemporary Indonesia - Ahyar, Muzayyin (INSTITUT AGAMA ISLAM NEGERI PALANGKA RAYA, 2018)
The collapse of the Suhartos authoritarian regime has brought Indonesia into a more democratic political landscape.